Commended English Language Arts Curriculum Guides, K-12 - National Council of Teachers of English, Urbana, IL.; National Council of Teachers of English, Urbana, IL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This guide, growing out of the annual evaluation by the National Council of Teachers of English (NCTE) of English Language Arts curriculum documents (K-12), presents exemplary curriculum documents from the years 1986-1989. The guide presents documents which were commended by the NCTE reviewers and which demonstrate substantive, procedural, or presentational features which can serve as illustrative examples for other schools or school districts. Entries in the guide include a description of the curriculum document, a commentary about its applicability, and information about its availability (cost, a contact person or office, and the appropriate address). Following an introduction, the guide is in four main sections. The guide's first section presents curriculum guides commended in 1988-89, the next section presents those commended in 1987, the following section those for 1986, and the fourth section presents the criteria for planning and evaluating English language arts curriculum guides. Information about the ERIC Document Reproduction Service concludes the guide. (SR)
ERIC Note: Prepared by the NCTE Commission to Evaluate Curriculum Guides and Competency Requirements.
Educational level discussed: Elementary Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Development; Curriculum Evaluation; Curriculum Guides; Demonstration Programs; Elementary Secondary Education; English Curriculum; Language Arts; Program Development; National Council of Teachers of English; Guides, Non-Classroom.; Reference Materials, Bibliographies